Loss of interleukin-1 beta is not protective in the lupus-prone NZM2328 mouse model - Loftus, Shannon N.; Liu, Jianhua; Berthier, Celine C.; Gudjonsson, Johann E.; Gharaee-Kermani, Mehrnaz; Tsoi, Lam C.; Kahlenberg, J. Michelle (Frontiers in Immunology, 2023)
Aberrant activation of the innate immune system is a known driver of lupus pathogenesis. Inhibition of the inflammasome and its downstream signaling components in murine models of lupus has been shown to reduce severity of disease. Interleukin-1 beta (IL-1β) is a pro-inflammatory cytokine released from cells following inflammasome activation. Here, we examine how loss of IL-1β affects disease severity in the lupus-prone NZM2328 mouse model. We observed a sex-biased increase in immune complex deposition in the kidneys of female mice in the absence of IL-1β that corresponds to worsened proteinuria. Loss of IL-1β did not result in changes in overall survival, anti-dsDNA autoantibody production, or renal immune cell infiltration. RNA-sequencing analysis identified upregulation of TNF and IL-17 signaling pathways specifically in females lacking IL-1β. Increases in these signaling pathways were also found in female patients with lupus nephritis, suggesting clinical relevance for upregulation of these pathways. Together, these data suggest that inhibition of the inflammasome or its downstream elements that block IL-1β signaling may need to be approached with caution in SLE, especially in patients with renal involvement to prevent potential disease exacerbation.